EXPERIMENTAL AND NUMERICAL INVESTIGATIONOF NATURAL CONVECTION IN TUBE BUNDLE - KARAR, OLA (2020)
Convective heat transfer inside 3-internal pipes bundle is investigated experimentally and through computational fluid dynamics approach. A series of experimentswere conducted to investigate the effect of heating medium temperature, flowrate and physical propertieson the rate of heat transferred to production fluid. It was found that with an increase in the heating fluid temperature a higher outlet temperature of production fluid was obtained. Runs at different flowrates of heating medium had a positive effect on the final temperature of production fluid as well, however the heat loss to surroundings increased as the bundle is not fully insulated. The developed Computational Fluid Dynamics model wasvalidated against the experimental data to furtherinvestigatethe natural convection inside the bundleusing ethylene glycol as heating medium and crude oil as production fluid. Ethylene glycol gave lower rates of heat transferand lower Nusselt numbers compared to waterwhen used as heating medium due to its lower heat capacity. However, it operates within a wide range as it has a higher boiling point than water. Based on the observation and the database provided for rate of heat transfer from the respective tubes, a modification to an existing Nusselt number was made for the range of temperature and flow rates used in the experiments. The proposed values for the constants a,m,nin the model (